(untitled) - Chaston, Ian (New York, 2004)
E-commerce for Small Businessuses both published research and real-world case studies to provide students with an understanding of the key aspects of managing e-commerce processes within small firms. Realistic, validated-through-research management models and theories reveal how appropriate e-commerce strategies can be used to enhance small business performance. This text will make an ideal course companion for undergraduate and postgraduate students studying e-commerce within the small business sector.
Keywords: Electronic commerce,Business enterprises,Small business; Management,Computer networks,Computer networks